Randomised controlled trial of fractionated and unfractionated prednisolone regimens for dogs with immune‐mediated haemolytic anaemia. (22nd June 2019) - Swann, James W; Szladovits, Balazs; Threlfall, Anna J; Garden, Oliver A; Chang, Yu‐Mei; Church, David B; Glanemann, Barbara
Abstract : Methods: A randomised non‐blinded non‐inferiority trial was conducted to determine whether treatment with an unfractionated regimen of oral prednisolone was inferior to a fractionated regimen for dogs with primary immune‐mediated haemolytic anaemia. Dogs received the same total daily dose of prednisolone as unfractionated (group 1, starting at 4 mg/kg orally once daily) or fractionated (group 2, starting at 2 mg/kg orally twice daily) doses. Questionnaires were administered to owners to assess adverse effects and quality of life (QoL). End points included survival to eight weeks, and changes in QoL and clinicopathological parameters over time. Results: Thirty‐nine dogs were enrolled in the study, of which 5 were withdrawn and 17 were assigned to each group. The number of cases recruited was insufficient to determine whether unfractionated treatment was inferior to fractionated. Total serum bilirubin decreased more rapidly in dogs in group 2, whereas polydipsia improved more rapidly in group 1. Blood pressure and score for polyuria were higher in dogs in group 2 over time, whereas lymphocyte concentration was lower. Conclusion: Administration of the same total daily dose of prednisolone as an unfractionated dose resulted in fewer adverse effects but the effect on survival could not be assessed in this study.